The possibility of creating an automated control system of the various military groups - Mikayilov, Telman Neman oğlu; Bayramov, Azad Agalar oğlu (Національний технічний університет "Харківський політехнічний інститут", 2019)
From the experience of war and armed conflicts that have taken place in recent times, it seems that the exchange of information in all the fields of warfare is very important in the military confrontation, which are conducted traditionally and basically using new methods of struggle. Given importance of this factor, leading states have increased their efforts to create a network command and control system of combat operations by utilizing new information technologies. Nowadays, automation of the command and control systems is an effective way of carrying out of military operations (combat operations), covering the Armed Forces command and control system from the operat ors of the arms sy stems to the top command. In this paper there have been analyzed the possibilities for data processing and its management of the Armed Forces and Weapons in the Automated Control System ( ACS). To create conditions for coordinated actions between typesof Army, the possibility of transform their response zones into a coordinated battlefield has been disclosed. During the decision-making process, it has been shown that the process of data collection, analysis and distribution is the most effective technological tool for modeling of operation.

З досвіду воєн і збройних конфліктів, що мали місце останнім часом, здається, що обмін інформацією в усіх сферах військових дій дуже важливий у військовому протистоянні, яке традиційно і в основному проводиться з використанням нових методів боротьби. З огляду на важливість цього чинника, провідні держави активізували свої зусилля зі створення мережевої системи управління бойовими діями з використанням нових інформаційних технологій. В даний час автоматизація систем командування і управління є ефективним способом проведення військових дій (бойових дій), що охоплюють систему управління збройними силами від операторів систем озброєння до вищого командування. У даній статті були проаналізовані можливості обробки даних і управління збройними силами і зброєю з використанням АСУ. Для створення умов для узгоджених дій між різними підрозділами була розкрита можливість перетворення їх зон реагування в скоординоване поле битви. У процесі прийняття рішення було показано, що процес збору, аналізу та поширення даних є найбільш ефективним технологічним інструментом для моделювання роботи.
Про можливість створення автоматизованих систем управління різних військових частин
Keywords: firedestructions means; special software; automation complex; засоби вогневого ураження; спеціальне програмне забезпечення; автоматизований комплекс